2017
DOI: 10.1590/s0102-865020170040000005
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study between standard and inside-out vein graft techniques on sciatic nerve repair of rats. Muscular and functional analysis

Abstract: Comparative study between standard and inside-out vein graft techniques on sciatic nerve repair of rats. Muscular and functional analysis 1 4-Experimental SurgeryActa Cir Bras. 2017;32(3):287-296 Abstract Purpose: To compare the functional result of standart vein grafts and inside-out vein graft technique on sciatic nerve repair. Methods: We used 24 male Wistar rats divided into 4 groups: control group (CG), standard vein graft group (SVG), Inside-out vein graft group (IOVG) and denervated Group (DG). SVG, IOV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 24 publications
2
15
0
2
Order By: Relevance
“…The choice of the venous tubulization technique associated with cell therapy, In this experiment, demonstrated better histomorphological and histomorphometric results in the vein filled with Platelet Rich Plasma groups (SVPRP e IOVPRP), coinciding with some authors who used other types of filling [13][14][15][16] . Thus, it can be suggested that the filling of the vein with biological materials, prevent venous lumen collapse, allowing for better biochemical communication between the nervous stumps, and thus favoring the axonal growth 4 .…”
Section: Acta Cir Bras 2017;32(8):617-625supporting
confidence: 55%
See 1 more Smart Citation
“…The choice of the venous tubulization technique associated with cell therapy, In this experiment, demonstrated better histomorphological and histomorphometric results in the vein filled with Platelet Rich Plasma groups (SVPRP e IOVPRP), coinciding with some authors who used other types of filling [13][14][15][16] . Thus, it can be suggested that the filling of the vein with biological materials, prevent venous lumen collapse, allowing for better biochemical communication between the nervous stumps, and thus favoring the axonal growth 4 .…”
Section: Acta Cir Bras 2017;32(8):617-625supporting
confidence: 55%
“…In theory, in cases of peripheral nerve damage such as neuropraxia or axonotmosis, where there was no complete rupture of the nerve, the presence of the neurovascular bundle in contact with the adventitia would provide a favorable microenvironment that could contribute to the repair process 16 . Thus, it can be suggested that laminin and the tunica adventitial, rich in collagen and trophic factors, in direct contact with the axons were not decisive to provide higher histomorphometric results compared to the standard technique 21,22 .…”
Section: Acta Cir Bras 2017;32(8):617-625mentioning
confidence: 99%
“…Due to its biomechanical properties, ES protects and facilitates axonal regeneration, and thus was previously used in peripheral nerve repair as a conduit or sleeve in the rat and rabbit models (Ayhan, Markal, Siemionow, Araneo, & Siemionow, 2003;Ayhan, Yavuzer, Latifo glu, & Atabay, 2000;FIGURE 4 Comparison of the maximal nerve conduction velocity-NCV (A) and somatosensory evoked potentials-SSEP (B) results between autograft controls (group 2, n = 4 nerves/group) and epineural sheath conduit (group 3, n = 4 nerves/group) at 6 months after sheep median nerve repair FIGURE 5 Representative images of toluidine blue staining of a distal segment of autograft controls (panel A) and epineural sheath conduit (panel B) at 6 months after sheep median nerve repair confirmed presence of myelinated axons Demirkan, Snyder, Latifoglu, & Siemionow, 1995;Karacaoglu, Yüksel, Peker, & Güler, 2001). Compared to other naturally occurring biomaterials, such as vein (Bueno et al, 2017;Nijhuis et al, 2013), artery (Itoh et al, 1996), muscle (Battiston, Tos, Conforti, & Geuna, 2007;Nijhuis et al, 2013), or bone (IJpma, Van De Graaf, & Meek, 2008), ES is the only material of the neural origin. This represents a potential advantage of the ESC over other natural and synthetic conduits, due to a high laminin expression (Siemionow et al, 2011), which provides neuropermissive microenvironment and facilitates Schwann cell attachment and axonal regeneration (Siemionow & Brzezicki, 2009;Siemionow, Bozkurt, & Zor, 2010).…”
Section: Discussionmentioning
confidence: 96%
“…Due to its biomechanical properties, ES protects and facilitates axonal regeneration, and thus was previously used in peripheral nerve repair as a conduit or sleeve in the rat and rabbit models (Ayhan, Markal, Siemionow, Araneo, & Siemionow, ; Ayhan, Yavuzer, Latifoğlu, & Atabay, ; Demirkan, Snyder, Latifoglu, & Siemionow, ; Karacaoglu, Yüksel, Peker, & Güler, ). Compared to other naturally occurring biomaterials, such as vein (Bueno et al, ; Nijhuis et al, ), artery (Itoh et al, ), muscle (Battiston, Tos, Conforti, & Geuna, ; Nijhuis et al, ), or bone (IJpma, Van De Graaf, & Meek, ), ES is the only material of the neural origin. This represents a potential advantage of the ESC over other natural and synthetic conduits, due to a high laminin expression (Siemionow et al, ), which provides neuropermissive microenvironment and facilitates Schwann cell attachment and axonal regeneration (Siemionow & Brzezicki, ; Siemionow, Bozkurt, & Zor, ).…”
Section: Discussionmentioning
confidence: 99%
“…A principal consequência da lesões de nervo periférico (PNI -sigla em inglês para peripheral nerve injury) é a perda definitiva da função do membro ou local afetado, sendo que muitas vezes o uso de transplante de nervo do próprio paciente, assim como a utilização de biomateriais em conjunto ou não com células-tronco, se tornam uma alternativa na busca da regeneração e retorno da função (BUENO et al, 2017;COONEY et al, 2016;GÄRTNER et al, 2014;HEI et al, 2017;MARCONI et al, 2012;ZHANG, T. et al, 2014;WANG et al, 2010;WANG et al, 2017).…”
Section: Utilização De Células-tronco Na Terapia Regenerativa De Lesãunclassified